PERANAN MOTIVASI DALAM MENINGKATKAN PRESTASI KERJA PADA BANK INDONESIA - Windy Adriana (JURNAL AKADEMIKA)
Bank Indonesia is an independent state institution, which has the duty to formulate and implement monetary policy, regulate and maintain the payment system, and regulate and supervise other banks. With the vision of â€œ trustworthy and respectabilityâ€, BI supports the profesionalism of the individual employee in performing tasks. To support the vision, the necessary human resources that are reliable and high-performance, where the motivation of leadership has an important role in improving work performance and job satisfaction, so that the vision and mission of the organization can be accomplished.